GOVERNING ISLAMIC EDUCATION IN A DECENTRALIZED SYSTEM: A COMPARATIVE STUDY OF PUBLIC SCHOOLS, ISLAMIC BOARDING SCHOOLS, AND PESANTREN IN WEST SUMATRA - Sandra, Ika; Arya Kurniawan, Rama; Alfian, Muhammad (STKIP Subang, 2026)
This study examines the implementation and management of Islamic education within a decentralized educational system in West Sumatra, Indonesia, specifically in the cities of Padang and Padang Panjang. The shift from a centralized to a decentralized governance structure in 1999 provided local governments with greater autonomy over education, allowing them to tailor educational policies to the needs of their communities. This research focuses on the role of local government in overseeing Islamic education in various school types, including public schools, Islamic boarding schools, and pesantren. Using a qualitative approach, the study collects data through interviews with key stakeholders such as education authorities, school principals, and teachers as well as document analysis from government and educational institutions. The findings highlight the diverse methods of implementing Islamic education in these cities and the challenges faced by local authorities in aligning Islamic education with both national curriculum standards and religious values. The study reveals the flexibility and adaptability of schools in West Sumatra in responding to the decentralization of education and offers insights into the intersection of policy, practice, and local values in shaping the educational landscape.